Rules of Oxidative Stress in Wound Healing - Arief, Handy (Universitas Wijaya Kusuma Surabaya, 2016)
Wound healing is a complex dynamic process characterized by a series of events that occur in almost all type of tissue damage. In the early phase of the inflammatory response, neutrophils and macrophages enters into the injured tissue and the cells produce reactive oxygen species that can give a beneficial or detrimental effects. Oxidative stress is a condition occurs that shows imbalance between prooxidant or free radical and antioxidant that have a function to maintain the condition of the tissue damage that occurs. So Oxidative stress occurs when the production of Reactive Oxygen Species occurring is higher than the antioxidants existing as an intrinsic defense. Reactive Oxygen Species and Reactive Nitrogen Species are important components in the healing process of wounds and is necessary to be in the state of homeostasis to prevent oksidatif stress. The major components of ROS are superoxide (O2â¢), hydroxyl radical (OHâ¢) and hydrogen peroxide (H2O2), which includes RNS are nitric oxide (NOâ¢), nitrous oxide (NO2â¢), nitroxyl anion (HNO) and peroxynitrite (ONOO-) which could be form by the reaction between superoxide and nitric oxide. The existence of excessive O2 amount in the wound and the presence of excess NO can increase the incidence of oxidative stress that interfere with wound healing process. Oxidative stress plays a role in the inflammatory phase, proliferation and remodeling phase by increasing angiogenesis and affect other cells including endothelial cells in secreting NO. So the strategy in controlling oxidative stress is by increasing antioxidant level which is a scavenger to free radical excessive superoxide formation so preventing interference with the wound healing process.Â